2004
DOI: 10.1093/jis/4.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Habitat disturbance and the diversity and abundance of ants (Formicidae) in the Southeastern Fall-Line Sandhills

Abstract: We examined habitat disturbance, species richness, equitability, and abundance of ants in the Fall-Line Sandhills, at Fort Benning, Georgia. We collected ants with pitfall traps, sweep nets, and by searching tree trunks. Disturbed areas were used for military training; tracked and wheeled vehicles damaged vegetation and soils. Highly disturbed sites had fewer trees, diminished ground cover, warmer soils in the summer, and more compacted soils with a shallower A-horizon. We collected 48 species of ants, in 23 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
3
21
1
3
Order By: Relevance
“…In contrast, Formicidae were more abundant in disturbed soil. This result suggests that this agricultural practice degraded the habitat for litter-dwelling species and at the same time, created an open and dry habitat that favored the Formicidae (Graham et al, 2004). A similar finding was found by Luz et al (2013), who reported a higher frequency of Formicidae in managed areas than in native forests in Northeast Brazil.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, Formicidae were more abundant in disturbed soil. This result suggests that this agricultural practice degraded the habitat for litter-dwelling species and at the same time, created an open and dry habitat that favored the Formicidae (Graham et al, 2004). A similar finding was found by Luz et al (2013), who reported a higher frequency of Formicidae in managed areas than in native forests in Northeast Brazil.…”
Section: Discussionsupporting
confidence: 79%
“…When we began studying species richness of ants at Fort Benning, we selected nine sites in three disturbance classes (light, moderate, and heavy). Species richness seemed to decrease monotonically with increasing disturbance [136]. But when we expanded the study to 40 sites across a much wider range of habitats and disturbance categories (bare ground with widely scattered trees and grasses to deciduous oak-hickory forest) we found the relationship was actually unimodal [32].…”
Section: Polynomial Regression and Data Smoothingmentioning
confidence: 83%
“…Frequent disturbances and low species richness characterise the landscape type of cultivated/exploited land. Negative effects of soil disturbances are shown both for ants (Graham et al, 2004) and for mollusks (Stiven, 1989). In contrast, verges usually have an intact grass sward, and can provide microhabitats for many ant species (Samways et al, 1997).…”
Section: Discussionmentioning
confidence: 99%